RELIGIOUS HARMONY AND GOVERNMENT IN INDONESIA - Khotimah Khotimah (Universitas Islam Negeri Sultan Syarif Kasim Riau, 2015)
Religious harmony, community and government is as a basic to create sustainable development in this country. Inter-religious dialogue under the program of FKUB of Indonesia can be as a modal and place of religious harmony and religious awarness where become intrinsic value of universal humanity. Furthermore, every adherent should understand their religion and also aware of religion diversity and diferencess. Theoritically, to understand the diversity and diferencess of adherent, there are three approaches are often used: theological, political and socio-cultural. Based on the basic principles and norms of theological and ethical, inter-religious dialogue is important thing, that should be done and sustainable developed